Density functional theory analysis of dopants in cupric oxide - Zhang, Zhen (2013)
Fabrication of both p-type and n-type cupric oxide is of great importance for the large-scale photovoltaic application. Our first-principles density functional theory calculations confirm that copper vacancy can lead to good p-type conduction in CuO, while oxygen vacancy is a deep donor. To investigate electrical conduction in CuO, we calculated the defect formation energies as well as their ionization levels for several potential acceptors and donors. Our results indicate that Li and Na are shallow acceptors and their formation energies are low in oxygen rich environment. However, it is also found that n-type conduction is relatively hard to induce by donors, as most donors have deep transition levels in the band gap and/or high formation energies. Hf and Zr have the shallowest ionization levels of around 0.2 eV below the conduction band minimum, but their formation energies are relatively high, limiting the electrical conductivity of doped CuO. Our study explains why it is hard to obtain n-type conduction in CuO.